Use of key word signing for children and adults with intellectual disability in an Irish context. Issue 3 (1st August 2019) - Byrne, Áine; Pyne, Jenna; Sheehan, Vanessa
Abstract : Purpose: Lámh is the Irish approach to key word signing (KWS). It was designed to support children and adults with intellectual and developmental disabilities (IDD) (including people with autism) and/or communication needs in Ireland. The purpose of this paper is to determine the level of Lámh use in a large organisation for children and adults with IDD and identify factors influencing use. Design/methodology/approach: An online questionnaire was distributed to 950 staff members in the aforementioned organisation. Findings: The response rate was 23 per cent ( n = 217), with the majority of respondents indicating a belief that all staff should know some key signs (96 per cent) and that Lámh has a positive impact on communication (89 per cent). In sum, 18 per cent of staff who supported a Lámh user reported that they rarely or never use signs. There was a significant association between client group (children or adults) and frequency of Lámh use by staff, with greater use reported in children's services. Research limitations/implications: Overall, a positive attitude towards Lámh was identified amongst staff within the organisation. Despite this, there is evidence of inadequate support for Lámh users, particularly in adult services. Identified barriers which impacted the implementation of Lámh included inconsistencies in organisational culture, levels of support and access to training. A consistent Lámh signing environment is crucial to the successful use of Lámh as a communication method. This study suggests that the level of support required to create a consistent signing environment may be underestimated. Originality/value: This is the first study to evaluate the reported use of key word sign in an Irish disability setting. The findings will be of benefit to any staff members supporting KWS users and, in particular, those involved in the provision of KWS training.